Persepsi Efektivitas Layanan dan Strategi Pemasaran BRILink terhadap Kepuasan Pelanggan di Sampit: Studi Kasus pada Grup BRILink HS Sampit - Nuraini, Naseha; Bambang Sutejo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This exploration depends on observational information as a survey which shows the consequences of the respondents' responses to the examination about BRILink HS Sampit. In response to this, the authors conducted observational data-based research with the goal of obtaining precise outcomes. This study aims to accomplish the following: 1) determining whether customer satisfaction is influenced by service, and 2) determining whether customer satisfaction is influenced by marketing strategy. Using a questionnaire with 100 respondents, data were gathered. While the information examination procedure utilized is quantitative investigation, utilizing numerous direct relapse. Purposive sampling was used as the sampling method.